PENERAPAN FOOD SAFETY PADA PENGOLAHAN PRODUK DIMSUM DI RESTORAN XIANG FU HAI VASA HOTEL SURABAYA - Marsheila Putri Ayu Dwi Hidayanti (JOURNAL SAINS STUDENT RESEARCH, 2026)
Background: Food safety is a crucial aspect of the food industry that involves cleanliness, sanitation, and food handling practices to prevent contamination and maintain product quality. Common errors in food handling—such as storage at improper temperatures, inadequate cooking, cross-contamination, and poor personal hygiene—can lead to foodborne illnesses. Purposes: This research aims to determine the implementation of food safety in the processing of dim sum products at Xiang Fu Hai Restaurant, Vasa Hotel Surabaya. Methods: The methodology employed in this study is qualitative descriptive, with data collection techniques involving observation, interviews, and documentation. Result: Xiang Fu Hai Restaurant has complied with Food Safety principles, ranging from the receipt of raw materials and storage processes to preparation, processing, and serving. However, several field obstacles remain, such as a lack of staff understanding regarding hygiene and sanitation procedures. Conclusion: Routine training and consistent supervision are necessary to enhance staff awareness and discipline in implementing food safety protocols optimally.